Ecomorphology in Kenya's Koobi Fora Formation: Reconstructing Early Pleistocene hominin paleoenvironments with 3D geometric morphometric analyses of bovid metapodials - Megan Malherbe; Nicole Webb; Magdalena Palisson-Kramer; Emmanuel K. Ndiema; David R. Braun; Martin Haeusler; Frances Forrest (Journal of Human Evolution, 2025)

Evaluating postintervention survival of free‐ranging odontocete cetaceans - Randall S. Wells; Deborah A. Fauquier; Frances M. D. Gulland; Forrest I. Townsend; Robert A. DiGiovanni (Marine Mammal Science, 2013)
Until recently, few data were available for evaluating postintervention survival of free‐ranging cetaceans receiving aid from humans through: rescue from stranding, with rehabilitation and release; rescue, rehabilitation and release of debilitated or entangled individuals that had not beached; rescue of entangled animals with immediate release; and rescue, transport, and release of out‐of‐habitat animals. Advances in medical diagnosis, husbandry and therapy have improved survival of rehabilitation cases, and advances in radio‐telemetry have improved postrelease monitoring. In total, 69 cases (1986–2010) were evaluated, involving 10 species of odontocete cetaceans with release data. Findings suggested a success criterion of surviving at least six weeks postrelease is useful in evaluating intervention strategies. No species had better success than others. Stranded beached cetaceans were less successful than free‐swimming rescued animals. Rehabilitated animals were less successful than those released without rehabilitation. Mass stranded dolphins fared better than single stranded animals. Old age, diminished hearing ability, and lack of maternal care were factors in several unsuccessful cases. Success is not clearly related to rehabilitation duration. Retaining healthy individuals from mass strandings until all animals are ready for release may reduce success for some. Transport durations for unsuccessful cases were greater than for successful cases.